A study of clinico-etiological profile and its association in patients of hemorrhoids and varicose veins - Gangwar, Aditya; Katiar, Vikash; Chaudhary, Ashish K.; Mishra, Yukteshwar (International Surgery Journal, 2025)
Background: Hemorrhoidal disease (HD) and chronic venous disease (CVD) are prevalent vascular conditions sharing mechanisms such as venous hypertension, pelvic congestion, and connective tissue degeneration. Despite their frequent overlap, concomitant occurrence is often under-recognized. This study aimed to estimate the prevalence of coexisting HD and CVD, identify associated risk factors, and assess clinical correlations to guide integrated management. Methods: This cross-sectional observational study was conducted at GSVM medical college, Kanpur between June 2023 and December 2024. A total of 140 patients were enrolled (70 HD, 70 CVD). Detailed demographic, clinical, and lifestyle data were collected. HD was assessed by digital rectal examination and graded using Goligher's classification, while CVD was confirmed by duplex ultrasonography and classified using CEAP criteria. Statistical analysis was performed using IBM SPSS version 29, with p<0.05 considered statistically significant. Results: Of the 140 patients, 60 (42.9%) presented with concomitant HD and CVD, 59 (42.1%) with isolated HD, and 21 (15.0%) with isolated CVD. A statistically significant association was observed between the presence of HD in patients with CVD (54.3%) compared to CVD in patients with HD (31.4%) (p=0.0043). (22.0%). Age>50 years (p=0.035) was significantly associated with the occurrence of concomitant disease. Conclusions: A substantial prevalence of concurrent HD and CVD was observed, particularly in older individuals with occupational risks. The higher occurrence of HD among CVD patients supports the role of systemic venous insufficiency in anorectal pathology. Routine screening for HD in CVD patients is recommended for comprehensive management.